LIFE AND DEATH FANTASY IN MATT HAIG’S THE MIDNIGHT LIBRARY - Sinda, Vatina; Assiddiqi, Hasbi; Pramita, Agry (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
AbstractThis study discusses the fantasy of life and death desire in Matt Haig’s The Midnight Library (2020). The aim of this research is: To find out what fantasy of life and death desire that represent id, ego, and superego of Matt Haig in The Midnight Library. This study uses a psychoanalysis approach, which is used to analyze the fantasy of life and death desire that can representative the id, ego, and superego of Matt Haig as an author regarding to life and death desire. The result of this study show the id is dominant among the ego and superego. prominently features id symbols, indicating a profound exploration of primal desires, instincts, and the unconscious mind, particularly evident in main character's arc. These id symbols, serve to unveil author's innermost wishes and untamed impulses, suspending societal norms and reality's constraints. Through id- driven narratives, readers witness Nora's pursuit of immediate gratification, navigating alternate lives driven solely by desires, devoid of moral judgment. Additionally, ego symbols reflect author's attempts to negotiate reality, while superego symbols embody societal ideals and moral judgments that conflict with author's id-driven desires.Keywords: Fantasy, Psychoanalysis, Matt Haig, Novel. Life and death.